1989
DOI: 10.1093/jmedent/26.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study of Competition Between United States Strains of Aedes albopictus and Aedes aegypti (Diptera: Culicidae)

Abstract: Mosquito abatement workers in Houston, Tex., and New Orleans, La., have observed that the recent introduction of Aedes albopictus (Skuse) has been accompanied by a decline and virtual disappearance of Ae. aegypti (L.). This suggests competitive displacement but contradicts the direction of displacement observed in native habitats of Ae. albopictus. The paper reports a series of laboratory studies on competition between U.S. strains of the two species. Larval survivorship, size, and development time were monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 0 publications
3
53
2
2
Order By: Relevance
“…albopictus in the United States were interpreted as indicating rapid local differentiation (Black et al 1988). Similar patterns of isozyme variation were detected at the heart of its native range in the tropics, suggesting that local genetic differentiation is characteristic of this species (Black et al 1989). Hence, many North American populations seem sufficiently isolated in climatically different habitats to allow for local adaptation if appropriate selection exists.…”
supporting
confidence: 52%
“…albopictus in the United States were interpreted as indicating rapid local differentiation (Black et al 1988). Similar patterns of isozyme variation were detected at the heart of its native range in the tropics, suggesting that local genetic differentiation is characteristic of this species (Black et al 1989). Hence, many North American populations seem sufficiently isolated in climatically different habitats to allow for local adaptation if appropriate selection exists.…”
supporting
confidence: 52%
“…albopictus, pois oscilações na abundância daquela espécie já ocorreram nesse país, principalmente nas décadas de 50 e 60. 1,10,15 Em 1986, um ano depois da detecção de municípi-os infestados por Ae. aegypti a Oeste do Estado de São Paulo, 6 foi registrada a introdução de Ae.…”
Section: Discussionunclassified
“…Early work suggested Ae. aegypti to be the superior competitor 7 . More recent works, however, have shown that Ae.…”
Section: Introductionmentioning
confidence: 99%